2005
DOI: 10.1007/s00122-005-0086-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and physical mapping of Pi37(t), a new gene conferring resistance to rice blast in the famous cultivar St. No. 1

Abstract: The famous rice cultivar (cv.), St. No. 1, confers complete resistance to many isolates collected from the South China region. To effectively utilize the resistance, a linkage assay using microsatellite markers (SSR) was performed in the three F2 populations derived from crosses between the donor cv. St. No. 1 and each of the three susceptible cvs. C101PKT, CO39 and AS20-1, which segregated into 3R:1S (resistant/susceptible) ratio, respectively. A total of 180 SSR markers selected from each chromosome equally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…Pi3(t) and Pi5(t), and Pi1 and Pi7(t) 45,49 ). In addition, several genes are suggested to be allelic or tightly linked (e.g., Pi2/Piz, Piz-t, and Piz-5 on chromosome 6, Pik, Pik-s, Pik-p, Pik-m, Pik-h, and Pik-g on chromosome 11, and Pita and Pita-2 on chromosome 12).…”
Section: Number Of Rice Blast Resistance Genesmentioning
confidence: 99%
“…Pi3(t) and Pi5(t), and Pi1 and Pi7(t) 45,49 ). In addition, several genes are suggested to be allelic or tightly linked (e.g., Pi2/Piz, Piz-t, and Piz-5 on chromosome 6, Pik, Pik-s, Pik-p, Pik-m, Pik-h, and Pik-g on chromosome 11, and Pita and Pita-2 on chromosome 12).…”
Section: Number Of Rice Blast Resistance Genesmentioning
confidence: 99%
“…1 confers partial resistance to Japanese and complete resistance to Chinese isolates of blast (Ezuka et al 1969a,b;Yunoki et al 1970;Chen et al 2005). Much of this resistance is due to the presence of Pi37 .…”
Section: B Last Caused By the Filamentous Ascomycetementioning
confidence: 99%
“…Stability of the constructs was checked as previously described (Qu et al 2003), and the constructs were then individually transformed into the highly blastsusceptible rice cultivar Q1063, following the methods elaborated by Hiei et al (1994). The reaction to blast infection of the primary transgenics (T 0 ) and their progeny (T 1 and T 2 ) was tested by artificial inoculation with isolate CHL1159 (Pan et al 2003;Chen et al 2005). The Pi37 donor St. No.…”
Section: Candidate Gene Cloningmentioning
confidence: 99%
“…For several decades, several genes of blast resistance were found that are effectively used to control rice blast disease in rice breeding and genetic studies (Chen et al, 2005;Ballini et al, 2008;Koide et al, 2009;McCouch et al, 1994 Piz genes in the tested rice germplasm, respectively. The previous studies described that the Pik-m of three Pik locus on chromosome 11 confer high and stable resistance to many…”
Section: Genetic Statistics and Similarity In Korean Landracesmentioning
confidence: 99%
“…Since then, the inheritance of resistance has been extensively studied, and over 70 major R genes have now been reported (Chen et al, 2005;Ballini et al, 2008;Koide et al, 2009). During the last few years, considerable progress has been made to understand molecular mechanisms of M. grisea infection to rice plants and rice blast R genes [Pit, Pib, Piz, Pik, Pik-m/Pik-p, Pita/Pita-2 (Hayashi et al, 2006), Piz-t (Hayashi et al, 2004;Zhou et al, 2006), Pi-d(t)2 (Chen et al, 2004), Pii (Jeon et al, 2003), Pik-m (Zhai et al, 2011), Pi39 , Pita (Jia et al, 2002 andJia et al, 2004), Pi9 , Pid2 (Chen et al, 2006), Pi2 , Pi36 , Pi37 , Pi5 (Lee et al, 2009) and Pi3 (Shang et al, 2009)] have been identified and characterized via map-based cloning or chromosome walking.…”
Section: Introductionmentioning
confidence: 99%